2013
DOI: 10.1210/en.2013-1484
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antenatal Synthetic Glucocorticoid on Glucocorticoid Receptor Binding, DNA Methylation, and Genome-Wide mRNA Levels in the Fetal Male Hippocampus

Abstract: The endogenous glucocorticoid (GC) surge in late gestation plays a vital role in maturation of several organ systems. For this reason, pregnant women at risk of preterm labor are administered synthetic glucocorticoids (sGCs) to promote fetal lung development. Animal studies have shown that fetal sGC exposure can cause life-long changes in endocrine and metabolic function. We have previously shown that antenatal sGC treatment is associated with alterations in global DNA methylation and modifications to the hipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 50 publications
0
49
0
Order By: Relevance
“…These glucocorticoid-induced changes in DNA methylation have been shown to remain into adulthood and are even transmitted to the next generation. It was also shown that glucocorticoid treatment during pregnancy can modify the transcriptional and epigenetic machinery of the developing fetal hippocampus particularly associated with modified glucocorticoid receptor (GR) DNA-binding and DNA-methylation (108). A study in rats, applying mild or strong stress during mid-gestation demonstrated that PS induced region-specific changes of global DNA-methylation in male and female offspring.…”
Section: Ps-induces Epigenetic Programmingmentioning
confidence: 99%
“…These glucocorticoid-induced changes in DNA methylation have been shown to remain into adulthood and are even transmitted to the next generation. It was also shown that glucocorticoid treatment during pregnancy can modify the transcriptional and epigenetic machinery of the developing fetal hippocampus particularly associated with modified glucocorticoid receptor (GR) DNA-binding and DNA-methylation (108). A study in rats, applying mild or strong stress during mid-gestation demonstrated that PS induced region-specific changes of global DNA-methylation in male and female offspring.…”
Section: Ps-induces Epigenetic Programmingmentioning
confidence: 99%
“…18,19 To evaluate the role of the synthetic glucocorticoid, dexamethasone, in modulating DNA modification patterns in immature enterocytes, H4 cells were exposed to dexamethasone for 48 h, and the global pattern of the modification change was examined ( Supplementary Fig. S3).…”
Section: Glucocorticoid Effects On Dna Modification In H4 Cellsmentioning
confidence: 99%
“…To investigate the direct consequences of excess prenatal glucocorticoid exposure on the epigenetic landscape of brain tissue, Matthews and colleagues exposed pregnant guinea pigs to the synthetic glucocorticoid betamethasone during periods of rapid neurogenesis and brain growth (Days 41–42 and 51–52 of pregnancy, respectively) [61]. DNA and RNA were extracted from offspring hippocampal tissue either on post-natal Day 52 or 65, and microarray analysis with Nr3c1 DNA immunoprecipitation and chip hybridization performed for those genes that demonstrated differential Nr3c1 DNA binding compared to control (unexposed) offspring.…”
Section: Dna Methylation Biomarkers Of Neurodevelopment Outcomementioning
confidence: 99%